EduFeed: A social feed to engage preliterate children in educational activities - Sobel, Kiley; Kovacs, Geza; McQuillen, Galen; Cross, Andrew; Chandrasekaran, Nirupama; Henry Riche, Nathalie; Cutrell, Ed; Morris, Meredith Ringel (Proceedings of CSCW 2017, Computer Supported Cooperative Work, 2017)
In this work, we present EduFeed, a system that enables preliterate children to explore an algorithmically-mediated social feed of learning exercises, select activities to engage in, and share them with their peers. We deployed EduFeed as a technology probe to three classrooms of ESL students in the first year of elementary school in India who had limited English literacy and limited experience with touchscreen technology. We found that children were able to self-direct their engagement with the system and were initially motivated by digital sharing, while social context surrounding the system in physical space was also important. Based on our design and probe deployment, we reflect on issues relevant to adapting the social feed paradigm to this context, such as ranking algorithms, physicality, immediacy, and bridging physical and digital collaborative experiences.